2001
DOI: 10.1074/jbc.m010928200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Functional Monomeric Form of the Bacteriophage T4 Dda Helicase

Abstract: The active form of many helicases is oligomeric, possibly because oligomerization provides multiple DNA binding sites needed for unwinding of DNA. In order to understand the mechanism of the bacteriophage T4 Dda helicase, the potential requirement for oligomerization was investigated. Chemical cross-linking and high pressure gel filtration chromatography provided little evidence for the formation of an oligomeric species. The specific activity for ssDNA stimulated ATPase activity was independent of Dda concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…Based on the crystal structures of the Bacillus stearothermophilus PcrA in the presence and absence of the nucleotides and DNA (19,20), Wigley and co-workers (20 -24) have found that the PcrA helicase functions as a monomer and that the structural and biochemical properties of the PcrA helicase are best explained by the "inchworm" mechanism. Consistent with this model, other helicases, such as UvrD (25), RecG (26), Dda (27,28), RecQ (29), BLM (30), WRN (31), and NS3h (32), could also function as a monomer. The crystal structures of NS3h (33), RecG (34), Rep (35), and E. coli RecQ (36) have revealed that these helicases are in the monomeric forms.…”
mentioning
confidence: 52%
“…Based on the crystal structures of the Bacillus stearothermophilus PcrA in the presence and absence of the nucleotides and DNA (19,20), Wigley and co-workers (20 -24) have found that the PcrA helicase functions as a monomer and that the structural and biochemical properties of the PcrA helicase are best explained by the "inchworm" mechanism. Consistent with this model, other helicases, such as UvrD (25), RecG (26), Dda (27,28), RecQ (29), BLM (30), WRN (31), and NS3h (32), could also function as a monomer. The crystal structures of NS3h (33), RecG (34), Rep (35), and E. coli RecQ (36) have revealed that these helicases are in the monomeric forms.…”
mentioning
confidence: 52%
“…Oligonucleotides and Antibodies-All oligonucleotides were purchased from Integrated DNA Technologies and purified (103). The sequences used were: Cy3-G4DNA (5Ј-T 15 GAG GGT GGG TAG GGT GGG TAA-Cy3-3Ј), a well characterized G4DNA-forming sequence based on a region of the c-MYC promoter (104); Cy3-T 20 (5Ј-T 20 -Cy3-3Ј); Cy3-Scr (5Ј-TGT TGT TGT TGT TGT TGT TGT TGA GTG TAG TTG AAG-Cy3-3Ј), a scrambled version of the G4DNA sequence; Cy3-PS-Scr (5Ј-T*G*T TGT TGT TGT TGT TGT TGT TGA GTG TAG TTG A*A*G -Cy3-3Ј), where the asterisk indicates a phosphorothioate linkage; 3Ј-Bio-G4DNA (5Ј-T 15 GAG GGT GGG TAG GGT GGG TAA-BioTEG-3Ј); 3Ј-Bio-ssDNA (5Ј-T 15 -BioTEG-3Ј); Cy3-Cy5-G4DNA (5Ј-Cy5-T 15 GAG GGT GGG TAG GGT GGG TAA-Cy3-3Ј); and Cy3-Cy5-Scr (5Ј-Cy5-TGT TGT TGT TGT TGT TGT TGT TGA GTG TAG TTG AAG-Cy3-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…The simplest explanation is that gp32-dda interactions induce an active form of the helicase. dda alone does not form stable quaternary structures in solution (48), and there is strong evidence that monomeric dda can unwind model DNA substrates (49). One possibility is that an oligomeric form of dda is required for strand displacement synthesis reactions and that gp32 binding triggers this oligomerization.…”
Section: Relationship Between Equilibrium and Kinetic Properties Of Gmentioning
confidence: 99%